Zinc-Laccase Biofuel Cell - Ahmad, Abdul Aziz; Othman, Raihan; Yusof, Faridah; Abdul Wahab, and Mohamad Firdaus (IIUM Engineering Journal, 2011)
A zinc-laccase biofuel cell adapting the zinc-air cell design features is investigated. A simple cell design configuration is employed: a membraneless single chamber and a freely suspended laccase in a quasi-neutral buffer electrolyte. The cell is characterised according to its open-circuit voltage, polarization profile, power density plot and discharge capacity at constant current. The biocatalytic role of laccase is evident from the polarization profile and power output plot. Performance comparison between a single chamber and dual chamber cell design is also presented. The biofuel cell possessed an open-circuit voltage of 1.2 V and delivered a maximum power density of 0.9 mW/cm2 at current density of 2.5 mA/cm2. These characteristics are comparable to biofuel cell utilising a much more complex system design. KEY WORDS (keyword)): Biofuel cell, Bioelectrochemical cell, Zinc anode, Laccase and Oxidoreductase. ABSTRAK: Sel bio-bahan api zink-laccase dengan adaptasi daripada ciri-ciri rekabentuk sel zink-udara telah dikaji. Sel dengan konfigurasi rekabentuk yang mudah digunapakai: ruangan tunggal tanpa membran dan laccase diampaikan secara bebas di dalam elektrolit pemampan quasi-neutral. Sel dicirikan berdasarkan voltan litar terbuka, profil polarisasi, plot ketumpatan kuasa dan kapasiti discas pada arus malar. Peranan laccase sebagai bio-pemangkin adalah amat ketara daripada profil polarisasi dan plot ketumpatan kuasa. Perbandingan prestasi di antara sel dengan rekabentuk ruangan tunggal and dwi-ruangan turut diketengahkan. Seperti dijangkakan, sel dengan rekabentuk ruangan tunggal menunjukkan kuasa keluaran yang lebih rendah jika dibandingkan dengan rekabentuk dwi-ruangan kemungkinan disebabkan fenomena cas bocor. Sel bio-bahan api ini mempunyai voltan litar terbuka 1.2 V dan memberikan ketumpatan kuasa maksima 0.9 mW/cm2 pada ketumpatan arus 2.5 mA/cm2. Ciri-ciri ini adalah sebanding dengan sel bio-bahan api yang menggunapakai rekabentuk sel yang jauh lebih rumit.